(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper presents the vibration spectra of a twin-screw compressor driven at various functioning regimes. The tests are performed to assess the potential of this rotary bladed machine as energy harvesting source. It is sought to determine the optimum spots on the compressor skid where piezoelectric harvesters can be placed, meeting the operational conditions. Like most of the industrial machinery, compressors exhibit inherent vibrations and heating during operation. The pulsatory effects of the compressed air trapped between the compressor’s male and female rotors inside the compressor also give birth to harmonics. It is important to evaluate the temperatures as well since piezoelectric harvesters should preferably operate close to room temperature so as not to deteriorate the material and avoid thermal hysteresis, which can ultimately lead to the loss of piezoelectric properties. The study herein involves acquiring vibrational data and representing it graphically as vibration spectra. An analytical model is also presented for calculating the main frequencies of the compressor, validated by the experimental data measurements. We also present laboratory tests with the piezoelectric harvester tuned near the male rotor’s frequency for achieving resonance conditions. The male rotor frequency was the most stable, with the highest amplitudes and of convenient value ( 83 Hz) for the tip mass required for decreasing the piezoelectric cantilever’s resonant frequency from 210 Hz.